Dubrovnik Devlet Arşivindeki Belgelere Göre XV.-XVI. Yüzyıllarda Doğu Adriyatik’te Dubrovnik Tekelleşmesi (4th International Balkan Studies Congress Proceedings, 2025)
There are relatively few studies on Dubrovnik-Ottoman relations in the 15th and 16th centuries, and those that exist primarily rely on the Ottoman State Archives in Istanbul, focusing mainly on the social, legal, or political aspe-cts of the evolving relationship. In this study, Ottoman documents found in the Dubrovnik State Archives, which have been examined in only a few studies so far, are used as primary sources. The study explores the impact of the economic and financial relations between Dubrovnik and the Ottoman Empire in the 15th and 16th centuries on Dubrovnik’s trade. The research examines themes such as trade, taxation, and patronage during the reigns of six different Ottoman sultans, using documents from the ascension of Sultan Mehmed II to the end of Sultan Murad III’s reign. It aims to uncover whether there were any changes or conti-nuities over time. Specifically, the study investigates the flexibility granted to Dubrovnik merchants regarding goods such as salt, wax, and grain, which were prohibited for sale (memnu meta) during periods of famine and war. It also exa-mines the resulting monopoly of Dubrovnik merchants in the Eastern Adriatic cities, which became their primary trading points as a natural consequence of this flexibility. Additionally, the study identifies tax practices that incentivized Dubrovnik trade and merchants. It was found that these taxes differed from tho-se imposed on non-Muslim and foreign merchants. The nature of Dubrovnik’s trade, which increased its commercial influence in the Eastern Adriatic due to the privileges granted in taxation and trade, is analyzed.